Madrasah Visit & Exchange of Knowledge 3.0: empowering tahfiz students through knowledge and skills transfer / Noor Azli Affendy Lee - Affendy Lee, Noor Azli (Academy of Language Studies, 2024)
The Aiding in Sustainable Skills Empowerment & Transfer (ASSETS) programme was held from 16th to 18th May 2024 at UiTM Penang Branch, Permatang Pauh Campus as a remarkable initiative aimed at fostering knowledge and skills among students from Maahad Riyadhil Quran (MRIQ). This collaborative effort involved various departments and clubs from UiTM Penang, including the English Language Club, Academy of Language Studies (ALS) and Department of Computer Science & Mathematics (JSKM) lecturers, and students from Kelab Budi Penyayang and Frisbee Club. It was also supported by Perpustakaan Tun Abdul Razak (PTAR) and Switch.